Cribriform adenocarcinoma of minor salivary gland: A report of two cases with an emphasis on cytology. Issue 12 (18th February 2014) - Gailey, Michael P.; Bayon, Rodrigo; Robinson, Robert A.
<x xml:space="preserve">Abstract</x> Cribriform adenocarcinoma of minor salivary gland (CAMSG) is a recently characterized low grade salivary gland malignancy that most commonly presents as a mass in the base of the tongue, frequently with regional lymph node metastasis. Given its relative rarity and overlapping cytomorphology, CAMSG may be confused with polymorphous low grade adenocarcinoma (PLGA) in minor salivary gland sites and papillary thyroid carcinoma (PTC) in cervical metastasis, in both fine‐needle aspiration and excisional specimens. As there are no cytology reports in the literature, we present two new cases of CAMSG and describe the aspiration cytology of the tumor taken from bench top aspirates, compare it with the histomorphology, and discuss the features that may help one avoid misdiagnosis of PTC in the setting of cervical lymph node metastasis. We found that like PTC, aspirates of CAMSG contain polymorphic fragments of epithelial cells arranged in monolayer sheets, papillary fronds and tips, and occasional cribriform configurations, and metachromatic stromal fragments, which may be misinterpreted as colloid. A background of myxoid/mucoid material also reminiscent of colloid was prominent. Differentiation from PLGA is more difficult based strictly on cytology. A review of the most current literature in relation to the molecular and immunohistochemical profiles, therapeutic options, and prognosis is also presented. It is critical for pathologists and clinicians to be aware of this tumor when presented with patients having a cervical lymph node mass in the absence of a primary tumor. Diagn. Cytopathol. 2014;42:1085–1090. © 2014 Wiley Periodicals, Inc.